Model Deployment Realistic Mathematics Education to Improve Student Learning Outcomes Grade 5 - Tobroni Tobroni; Rasilah Rasilah; Widiyanti Widiyanti (Journal of Mathematics Instruction, Social Research and Opinion, 2023)
This study aims to improve learning outcomes by applying learning models to Realistic Mathematic Education on material for arithmetic operations on fractions in class V SDN 1 Karangkendal, Kapetakan District, Cirebon Regency. This research is a Classroom Action Research conducted in 3 cycles. The subjects of this study were 29 grade 5 students at SDN 1 Karangkendal, Kapetakan District, Cirebon Regency. Research data was collected through tests. This data analysis uses a qualitative descriptive analysis technique. The results showed increased learning outcomes in fifth-grade students at SDN 1 Karangkendal, Kapetakan District, Cirebon Regency, through a learning model, Realistic Mathematic Education. The increase in student learning outcomes is shown by the increasing number of students who meet the Minimum Mastery Criteria scores. In cycle one there were 62.1% of students achieved the Minimum Mastery Criteria scores. Then, in cycle two there were 75.9% of students had achieved the Minimum Completeness Criteria score; in cycle three, 86.2% of students had achieved the Minimum Mastery Criteria score. Based on these results, there is an increase in student learning outcomes with the application of learning models Realistic Mathematic Education on material for arithmetic operations on fractions at SDN 1 Karangkendal, Kapetakan District, Cirebon Regency.